Haemodynamic changes induced by short- and long-term sodium chloride or sodium bicarbonate intake in deoxycorticosterone-treated rats - Zicha, Josef; Kuneš, Jaroslav (Acta physiologica Scandinavica, 1994)
The contribution of chloride to the haemodynamic changes of salt-dependent deoxycorticosterone (DOC) hypertension was studied in young Wistar rats subjected to dietary loading with sodium chloride (NaCl) or sodium bicarbonate (NaHCO3). Mean arterial pressure (MAP), cardiac output, systemic resistance (TPR) and arterial rigidity (estimated from pulse pressure/stroke volume ratio, PP/SV) were determined in conscious chronically cannulated rats. DOC-induced increase of MAP and TPR appeared earlier in NaCl-loaded than in NaHCO3-loaded rats. After 4-6 weeks of hypertensive treatment MAP, TPR and PP/SV ratio were higher in DOC-treated rats fed NaCl diet than in those fed NaHCO3 diet. In contrast, after a long-term hypertensive regimen (lasting for 7-9 weeks) there was no significant difference in either MAP or TPR between rats loaded with NaCl or NaHCO3. On the other hand, DOC hypertension induced by a long-term feeding of NaHCO3 diet was not associated with an increase of arterial rigidity which was characteristic for DOC-NaCl hypertensive rats. Thus, a sufficiently long selective dietary sodium loading is capable to increase the systemic resistance but not to alter the arterial rigidity. This was also confirmed by a comparison of blood pressure-matched DOC hypertensive rats fed NaCl or NaHCO3 diets. These animals did not differ in the degree of systemic resistance elevation but the arterial rigidity was increased only in NaCl-loaded rats.
Keywords: hydrogenuhličitan sodný; potkani Wistar; Desoxycorticosterone; minutový srdeční výdej; krevní tlak; kuchyňská sůl; Rats, Wistar; Vascular Resistance; Pulse; Rats; zvířata; Animals; Hypertension; pulz; deoxykortikosteron; Male; hypertenze; hemodynamika; mužské pohlaví; Cardiac Output; dieta; Hemodynamics; Diet; cévní rezistence; Blood Pressure; Sodium Chloride, Dietary; krysa rodu Rattus; Sodium Bicarbonate